Molecular genetic characterization of myeloid neoplasms with idic(X)(q13) and i(X)(q10) - Brunetti, Marta; Andersen, Kristin; Trøen, Gunhild; Micci, Francesca; Spetalen, Signe; Lenartova, Andrea; Tandsæther, Maren Randi; Panagopoulos, Ioannis (Frontiers in Oncology, 2024)
Background/AimIsodicentric [idic(X)(q13)] and isochromosome [i(X)(q10)] are infrequent aberrations in neoplastic diseases. The former is mainly reported in elderly women with myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML), whereas the latter is mostly found as a secondary aberration or part of complex karyotypes in various types of neoplasms, including MDS and AML. Here, we present the molecular genetics and clinical features of six patients with myeloid neoplasia and the above-mentioned aberrations.Patients and MethodsArray comparative genome hybridization (aCGH) and next-generation sequencing (NGS) myeloid panel were used to examine genetic alterations in five bone marrow samples containing neoplastic cells carrying idic(X)(q13) and one sample with i(X)(q10).ResultsThe breakpoints of idic(X)(q13) were clustered within a 200 kbp region encompassing FAM236B, DMRTC1B, and DMRTC1. The breakpoint of i(X)(q10) was identified within a 112 kbp region on sub-band p11.22 containing SSX2, SSX2B, and SPANXN5. Pathogenic variants of TET2 were identified in four cases, SF3B1 in three cases, ASXL1 and SRSF2 in two cases each, whereas STAG2, RUNX1, U2AF1, and TP53 pathogenic variants were detected in only single cases.ConclusionsThe breakpoints of idic(X)(q13) are within a 200kbp. i(X)(q10) in our study turned out to be a cryptic idic(X)(p11) aberration, reported for the first time here. TET2, SF3B1, ASXL1, or SRSF2 were highly prevalent in patients with idic(X)(q13)/i(X)(q10) abnormalities and were often associated with a worse prognosis.